THE PATHOPHYSIOLOGY AND MANAGEMENT OF XEROSTOMIA: A COMPREHENSIVE REVIEW - Raja, Ricky Ferdian; Chuan, How Kim; Halim, Susanna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
ABSTRACT Xerostomia, or more commonly known as dry mouth, is a common clinical condition that significantly affects oral comfort and health, characterized not only by the subjective sensation of dryness in the oral cavity but also by an objective decrease in the measured function of the salivary glands. Its etiology is multifactorial, often related to the side effects of more than hundreds of types of drugs, the consequences of radiotherapy to the head and neck area, manifestations of systemic diseases such as Sjögren's Syndrome and diabetes, and the natural aging process. This decrease in the quantity and quality of saliva directly interferes with the natural defense mechanisms of the mouth, increasing the risk of rampant dental caries, opportunistic infections such as oral candidiasis, and causing significant difficulties in mastication, deglutition and phonation, which ultimately negatively impact the quality of life of the sufferer. Therefore, effective management of xerostomia requires a comprehensive multidisciplinary approach, starting from an accurate diagnosis through anamnesis, clinical examination and sialometry, to the implementation of a treatment strategy tailored to the cause and severity, and ongoing patient education. This comprehensive perspective article aims to provide an in-depth review of the etiology, diagnostic approaches, and current spectrum of xerostomia management, highlighting recent advances in therapeutic modalities including salivary stimulants, artificial saliva, and mucosal protective agents as well as strategies for the prevention of oral complications. Particular attention is paid to the importance of an interdisciplinary perspective, emphasizing the vital role of collaboration between dentists, general practitioners/specialists, and pharmacists in developing a holistic and integrated patient care plan to improve the oral health and quality of life of individuals affected by xerostomia. ABSTRAKXerostomia, atau yang lebih dikenal dengan sebutan mulut kering, merupakan kondisi klinis umum yang secara signifikan memengaruhi kenyamanan dan kesehatan mulut, ditandai tidak hanya oleh sensasi subjektif kekeringan di rongga mulut tetapi juga oleh penurunan objektif fungsi kelenjar ludah yang terukur. Etiologinya multifaktorial, sering kali terkait dengan efek samping dari lebih dari ratusan jenis obat, konsekuensi radioterapi pada area kepala dan leher, manifestasi penyakit sistemik seperti Sindrom Sjögren dan diabetes, serta proses penuaan alami. Penurunan kuantitas dan kualitas air liur ini secara langsung mengganggu mekanisme pertahanan alami mulut, meningkatkan risiko karies gigi yang merajalela, infeksi oportunistik seperti kandidiasis oral, dan menyebabkan kesulitan yang signifikan dalam mengunyah, menelan, dan bersuara, yang pada akhirnya berdampak negatif pada kualitas hidup penderitanya. Oleh karena itu, penanganan xerostomia yang efektif memerlukan pendekatan multidisiplin yang komprehensif, mulai dari diagnosis yang akurat melalui anamnesis, pemeriksaan klinis dan sialometri, hingga penerapan strategi pengobatan yang disesuaikan dengan penyebab dan tingkat keparahan, serta edukasi pasien yang berkelanjutan. Artikel perspektif yang komprehensif ini bertujuan untuk memberikan tinjauan mendalam tentang etiologi, pendekatan diagnostik, dan spektrum penanganan xerostomia saat ini, yang menyoroti kemajuan terkini dalam modalitas terapi termasuk stimulan saliva, saliva buatan, dan agen pelindung mukosa serta strategi untuk pencegahan komplikasi oral. Perhatian khusus diberikan pada pentingnya perspektif interdisipliner, yang menekankan peran penting kolaborasi antara dokter gigi, dokter umum/spesialis, dan apoteker dalam mengembangkan rencana perawatan pasien yang holistik dan terintegrasi untuk meningkatkan kesehatan mulut dan kualitas hidup individu yang terkena xerostomia.